Affluence in Poverty: The Prideful Nigerian prosperity Gospel (Ευαγγέλιο Eυημερίας [Evangélio Evimerías]), in Light of the Laodicean Church Experience, Revelation 3:16–22 - Osaji-Nwafili, Stephen C. (IGWEBUIKE: African Journal of Arts and Humanities, 2023)
The contemporary Nigerian Christian society is suffused with various shades of prosperity gospel (eσαγγέλιο εσημερίας [evangélio evimerías]), garbed with quests for materialism. This brand of gospel which references faith in God, as a panacea for poverty eradication, gateway to health stability and victory over spiritual warfare, has produced very uncomfortable superficialities of religious attitudes among Nigerian Christians. Tracing its origin and growth, the paper highlights the prideful lushness and challenges of the trend in Nigeria, in comparison with the prideful status of the Laodicean church, in Rev. 3:14-22. Referencing the materialistic and physical health attitude, devoid of spiritual health in the Laodicean socio-religious society, the paper further compares the trend with the specters of materialism and corruption in the Nigeria prosperity gospel. Thus, with the impoverished state of the nation’s economy, and the constant efforts of Nigerians, in quests for freedom from impoverishments, many cling to this theological perceptive in attempts to bridging the gulch of class and social inequalities in Nigeria. The resultant consequence has been the problem of materialism, false religious identities, free display of fake ministers and pseudo-religiosities becoming endemic in Nigerian churches. There is therefore the need for Christianity in Nigeria to retrace her steps back to a genuine and gratifying affluence, in a spirituality that should be Christ oriented.
free
Keywords: Affluence; Laodicean Church; Nigeria; Poverty; Prideful; Prosperity Gospel